Mangroves restoration: youth challenge / Nor Alwani Omar - Omar, Nor Alwani (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2019)
Mangroves are critical coastal ecosystems that impact our lives. They nourish biodiversity as nursery grounds for many coastal and marine species as well as support fisheries. On April 20, 2019, Persatuan Siswa-Siswi Sains Matematik (PERSIK) together with Persatuan Pendidikan dan Kebajikan Nelayan Pantai Malaysia (JARING) had organized a mangrove restoration programme entitled Mangrove Planting for the Future. This programme aimed to enhance the awareness of the mangroves value among university students and to support the go green campaign by the government. The students were given an exposure about the benefits of mangrove as coastal defense, nesting/breeding habitat for fish and shellfish, and carbon storage.